Improving Science Literacy Skills Using a Guided Inquiry Learning Model in Science Education for Grade IV A at SDN Rawamangun 12 Pagi : Meningkatkan Kemampuan Literasi Sains Dengan Menggunakan Model Pembelajaran Inkuiri Terbimbing Pada Pembelajaran IPA Kelas IV A SDN Rawamangun 12 Pagi - Damayanti Firdaus, Efrida; Winarni, Susi; Amri, Mira Amelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve students’ scientific literacy skills in science learning through the implementation of the Guided Inkuiri learning model in Grade IV A at SDN Rawamangun 12 Pagi. The study was motivated by the low level of students’ scientific literacy in explaining phenomena, designing investigations, and interpreting scientific data. The research used the Classroom Action Research design based on Kemmis and McTaggart's model, consisting of two cycles: planning, action, observation, and reflection. The subjects were 31 fourth-grade students. Data were collected through scientific literacy tests, observation sheets, and documentation. The results showed an improvement in students’ scientific literacy after the implementation of the Guided Inkuiri model. In Cycle I, the percentage of students’ scientific literacy achievement was 75%, which had not reached the target. After improvement in teaching strategies, Cycle II increased to 81%, exceeding the minimum criterion of 80%. The improvement from Cycle I to Cycle II was 6%. These findings indicate that the Guided Inkuiri learning model is effective in improving students’ scientific literacy by promoting active involvement, critical thinking, and evidence-based learning in science instruction. Keywords: Guided Inkuiri Learning Model; Scientific Literacy; Classroom Action Research.